Virological evidence of the impact of non-pharmaceutical interventions against COVID-19 in Ecuador, a resource-limited setting - Andres Moreira-Soto; Alfredo Bruno; Doménica de Mora; Michelle Paez; Jimmy Garces; Ben Wulf; Anna-Lena Sander; Maritza Olmedo; Maria José Basantes Mantilla; Manuel Gonzalez Gonzalez; Solon Alberto Orlando; Silvia Salgado Cisneros; et al. (Emerging Microbes and Infections, 2023)
Ecuador had substantial COVID-19-mortality during 2020 despite early implementation of non-pharmaceutical interventions (NPIs). Resource-limited settings like Ecuador have high proportions of informal labour which entail high human mobility, questioning efficacy of NPIs. We performed a retrospective observational study in Ecuador’s national reference laboratory for viral respiratory infections during March 2020–February 2021 using stored respiratory specimens from 1950 patients, corresponding to 2.3% of all samples analysed within the Ecuadorian national surveillance system per week. During 2020, detection of SARS-CoV-2 (Pearson correlation; r = −0.74; p = 0.01) and other respiratory viruses (Pearson correlation; r = −0.68; p = 0.02) by real-time RT–PCR correlated negatively with NPIs stringency. Among respiratory viruses, adenoviruses (Fisher’s exact-test; p = 0.026), parainfluenzaviruses (p = 0.04), enteroviruses (p < 0.0001) and metapneumoviruses (p < 0.0001) occurred significantly more frequently during months of absent or non-stringent NPIs (characterized by <55% stringency according to the Oxford stringency index data for Ecuador). Phylogenomic analyses of 632 newly characterized SARS-CoV-2 genomes revealed 100 near-parallel SARS-CoV-2 introductions during early 2020 in the absence of NPIs. NPI stringency correlated negatively with the number of circulating SARS-CoV-2 lineages during 2020 (r = −0.69; p = 0.02). Phylogeographic reconstructions showed differential SARS-CoV-2 dispersion patterns during 2020, with more short-distance transitions potentially associated with recreational activity during non-stringent NPIs. There were also fewer geographic transitions during strict NPIs (n = 450) than during non-stringent or absent NPIs (n = 580). Virological evidence supports that NPIs had an effect on virus spread and distribution in Ecuador, providing a template for future epidemics in resource-limited settings and contributing to a balanced assessment of societal costs entailed by strict NPIs.